CASTELFRANCO, Diego. Dios y libertad. Félix Frías y el surgimiento de una intelectualidad y un laicado católico en la Argentina del siglo XIX. Rosario: Prohistoria ediciones. 2019. 384 páginas. ISNB: 978-987-4963-22-2. - Gabirondo, Julieta Constanza (Estudios del ISHiR, 2021)
God and freedom. Félix Frías and the emergence of a Catholic intelligentsia and laity in 19th century Argentina is a book by the historian Diego Castelfranco. The author will carry out a biographical work that allows to give an account of the journey of one of the intellectuals of the Generation of 37 to broaden the look towards other themes of the time such as the place that the Catholic religion should occupy and its link with the State. The networks of sociability, the social contexts of the different countries through which Frías traveled and the political languages ​​are of vital importance in this work.